PERAN DINAS TENAGA KERJA DALAM PENEMPATAN TENAGA KERJA LOKAL DI KOTA PEKANBARU TAHUN 2012-2013 - Riauni, Margaretha; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to identify and analyze the role of Local Government in the fight for the interests of the local workforce, especially the City of Pekanbaru. The background of this study is the high number of job seekers and the high rate of competition in getting jobs with restricted jobs. In addition, the object disobedience local employment policies to the policies is the background of this study does.This study used a qualitative approach in obtaining and analyzing the data, to the data analysis and the theory of the role of organizational policies form the basis for the study of data analysis. The withdrawal technique informant informant conducted with a purposive approach, the data in this study was obtained through interviews and observation techniques and study documentation. Descriptive data were analyzed during the study.The results of this study prove that the Department of Labor Pekanbaru agency given authority as appropriate Local Regulation No. 04 Year 2002 on Local Employment has made efforts such as local employment Canvasing Job Fair Job Market (Job Fair), Appropriate Technology Training, Entrepreneurship Training, Intensive productive and Infrastructure, Job Fair On Line, Training Skills Seeker work. In an effort to local employment, the Department of Labor is also faced with the constraints of lack of infrastructure in order to prepare a ready workforce, the instructor constraints and budget constraints. In addition, the Department of Labor was also faced with the constraints of manpower and lack of quality jobs.Keywords: Roles, Policies, and Labour